17 beta-estradiol increases intracellular free calcium concentrations of human vascular endothelial cells and modulates its responses to acetylcholine - (:unkn) unknown (INFORMA HEALTHCARE, 1997)
In this study, we have investigated the effect of (17)beta-estradiol (E2) on intracellular free calcium concentrations ([Ca2+](i)) in human umbilical vein endothelial cells (HUVEC) using fura-2 fluorescence, E2 at concentrations of 1nM-1 mu M was added subsequently to HUVEC cultures which were either deprived of estrogens or preincubated with E2 (100 nM) for 23 hours, In both groups of cultures, E2 stimulated significant increases in [Ca2+](i) in a dose-dependent manner, The effects were more prominent in E2-deprived cells, Preincubation of cells with tamoxifen or the presence of it in the buffer during the experiments did not inhibit the response of the cells to E2, Experiments performed in Ca2+ free/EGTA buffer yielded transient increases in [Ca2+](i) suggesting release of Ca2+ from intracellular stores was responsible for the initial peak, while sustained elevations were supported by Ca2+ influx from the extracellular space, Addition of La3+ abolished the sustained [Ca2+](i) elevations, Carbachol (CCh) (1nM, 100 nM) did not induce changes in [Ca2+](i) of estrogen-deprived cells but produced significant increases in [Ca2+](i) of the same cells after incubation with E2 for 30 minutes, The cultures which were preincubated with E2 for 24 hours responded to carbachol directly, The results of our study indicate that E2 may modulate the functions of endothelial cells after only a brief exposure and also may be necessary for the response to acetylcholine especially at low concentrations.
Keywords: endothelium; 17 beta-estradiol; acetylcholine; cytosolic free Ca2+; ATHEROSCLEROTIC CORONARY-ARTERIES; MUSCARINIC RECEPTORS; SMOOTH-MUSCLE; INOSITOL TRISPHOSPHATE; POSTMENOPAUSAL WOMEN; ESTROGEN; RELEASE; RABBIT; PROSTACYCLIN; BINDING